PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK MIXUE - Fooza Hasna Madani; Helin G Yudawisastra; Perwito Perwito (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2025)
This study aims to examine the effect of product quality and brand image on purchase decisions among consumers at the Mixue outlet in Kopo TKI III Bandung branch. Data were collected through questionnaires and analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) with the SmartPLS 4 application. A total of 359 respondents were selected using accidental sampling from consumers who had previously made purchases at the Mixue Kopo TKI III Bandung outlet. The results show that product quality has a significant effect on purchase decisions, as does brand image. Simultaneously, product quality and brand image significantly influence consumers' purchase decisions. The research variables contribute 75.6% to the model, while the remaining variance is influenced by other variables not included in this study.